2017
DOI: 10.5812/ircmj.58765
|View full text |Cite
|
Sign up to set email alerts
|

Does Alpha-Lipoic Acid Comsumption Improve Lipid Profile In Patients With Stroke? A Randomized, Double Blind, Placebo-Controlled Clinical Trial

Abstract: Background: Having a stroke, which is a devastating condition, is a major cause of deaths worldwide and is also accountable for long time disability with high personal and social cost in adults. Hyperlipidemia plays an important role in atherothrombosis, which is the precursor to stroke. One way for decreasing the risk of a stroke is treatment of dyslipidemia. Alpha-lipoic acid (ALA) is an eight-carbon, sulfur-containing compound with antioxidant properties and effective in protecting against hypercholesterole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…For LDLcholesterol, we also observed significant difference between the pre-sensitivity pooled WMD (−10.46 mg/dL; 95% CI, −21.01, 0.09) and post-sensitivity pooled WMD (−13.65 mg/ dL; 95% CI, −25.09, −2.21) after removing Manolescu et al [20] study. Also, we found for HDL-cholesterol a significant difference between the pre-sensitivity pooled WMD (−3.02 mg/dL; 95% CI, −20.18, 14.14) and post-sensitivity pooled WMD (−11.39 mg/dL; 95% CI, −21.77, −1.02) after removing Mohammadi et al [14] study (Table 3).…”
Section: Effects Of Ala Supplementation On Fasting Glucose and Lipid Profilesmentioning
confidence: 68%
See 2 more Smart Citations
“…For LDLcholesterol, we also observed significant difference between the pre-sensitivity pooled WMD (−10.46 mg/dL; 95% CI, −21.01, 0.09) and post-sensitivity pooled WMD (−13.65 mg/ dL; 95% CI, −25.09, −2.21) after removing Manolescu et al [20] study. Also, we found for HDL-cholesterol a significant difference between the pre-sensitivity pooled WMD (−3.02 mg/dL; 95% CI, −20.18, 14.14) and post-sensitivity pooled WMD (−11.39 mg/dL; 95% CI, −21.77, −1.02) after removing Mohammadi et al [14] study (Table 3).…”
Section: Effects Of Ala Supplementation On Fasting Glucose and Lipid Profilesmentioning
confidence: 68%
“…Zhao et al [13] demonstrated the beneficial effects of ALA supplementation for 3 weeks, in significantly decreasing serum triglycerides, total-and LDLcholesterol levels among patients diagnosed with acute cerebral infarction. Moreover, a 12-week supplementation with 600 mg ALA by patients experienced a stroke showed lowering impact on lipid profiles [14]. There are still studies with discrepant results.…”
Section: Effects Of Ala Supplementation On Lipid Profilesmentioning
confidence: 98%
See 1 more Smart Citation
“…It was observed that α‐LA administration in obese patients with stroke attenuated lipid profile impairment compared to placebo by reducing LDL (23 mg/dl), TG (24 mg/dl), plasma total cholesterol (48.5 mg/dl), and increasing HDL (13 mg/dl). In general, it might be concluded that α‐LA is a potent agent in decreasing adiposeness, cellular TG secretion, expression of lipogenic and lipoprotein genes, as well as ameliorating insulin resistance (Mohammadi et al, 2017a) (Table 2).…”
Section: Clinical Trial Studiesmentioning
confidence: 99%